The meaning of symbols in drawings in the context of the military conflict in Ukraine - Ewelina J. Konieczna; Viktoriia Kiriakova (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
Research objective: To recognize the symbolism of drawings of the Ukrainian children who experienced the situation of war and necessity of emigrating from their mother country and to compare them with the content of drawings made by Polish children at the same time, that it is in the first months following the outbreak of the war in Ukraine; The research problem and methods: What symbols can be identified in the drawings made by children of both nationalities and what their meaning is in the context of the war in Ukraine? The study applied the method of drawing and interview; Th e process of argumentation: Reconstruction of the symbolic meanings of drawings in the cultural context in the conditions of the military conflict in Ukraine; Research results: It was possible to identify symbols of idiosyncratic character in the drawings of the Ukrainian children, that are connected with the outbreak of the war in this country (e.g., destroyed houses, missiles, rockets). In the drawings of the children of both nationalities, it was also possible to recognize symbols of neutral meaning, which - however - in the case of the Ukrainian children's drawings made reference to the situation of war (e.g. an umbrella as protection against missiles). Interpretation of the drawings was carried out according to one schema, taking into account separate cultural contexts (Polish and Ukrainian), as well as the child's individual experience, which was demonstrated using a drawing by a 12-year-old Ukrainian girl; Conclusions, innovations, and recommendations: A drawing can off er an alternative method of learning about and making an attempt to understand a child, especially one who has found himself/herself in a difficult situation in life. Znaczenie symboliki rysunku w kontekście konfliktu zbrojnego w Ukrainie Cel naukowy: Poznanie symboliki rysunków dzieci ukraińskich, które doświadczyły sytuacji wojny i konieczności emigracji z kraju oraz porównanie ich z treścią rysunków dzieci polskich, wykonanych w tym samym czasie, tj. w pierwszych miesiącach od momentu wybuchu wojny w Ukrainie. Problem i metody badawcze: Ja kie symbole można zidentyfi kować na rysunkach dzieci obu narodowości i jakie jest ich znacznie w kontekście wojny w Ukrainie? W badaniu wykorzystano metodę rysunku i wywiadu. Proces wywodu: Re konstruowanie znaczeń symboliki rysunku w kontekście kulturowym, w warunkach konfliktu zbrojnego w Ukrainie. Wyniki analizy naukowej: Na rysunkach dzieci z Ukrainy zidentyfikowano symbole o charakterze idiosynkratycznym, tzn. takie, które związane były z wybuchem wojny w tym kraju (np. zniszczone domy, pociski rakietowe itp.). Na rysunkach dzieci obu narodowości rozpoznano też symbole o neutralnym znaczeniu, które jednak w przypadku rysunków dzieci ukraińskich także odnosiły się do sytuacji wojny (np. "parasol" jako ochrona przed uderzeniem pocisku). Interpretacje rysunków zostały przeprowadzone według jednego schematu, z uwzględnieniem odrębnego kontekstu kulturowego (polskiego i ukraińskiego) oraz indywidualnych doświadczeń autora/autorki rysunku, co zaprezentowano na przykładzie pracy 12-letniej dziewczynki z Ukrainy. Wnioski, innowacje, rekomendacje: Rysunek może być alternatywną metodą poznania i próby (z)rozumienia dziecka, szczególnie będącego w trudnej sytuacji życiowej.